VISCOSITY OF ALBITE MELT AT HIGH PRESSURE AND HIGH TEMPERATURE - Suzuki A.; Ohtani E.; Funakoshi K.; Terasaki H.; Kubo T. (My University, 2002)
The viscosity of albite (NaAlSi3O8) melt was measured at high pressure by the in situ falling-sphere method using a high-resolution X-ray CCD camera and a large-volume multianvil apparatus installed at SPring-8. This system enabled us to conduct in situ viscosity measurements more accurately than that using the conventional technique at pressures of up to several gigapascals and viscosity in the order of 100 Pa s. The viscosity of albite melt is 5.8 Pa s at 2.6 GPa and 2.2 Pa s at 5.3 GPa and 1973 K. Experiments at 1873 and 1973 K show that the decrease in viscosity continues to 5.3 GPa. The activation energy for viscosity is estimated to be 316(8) kJ mol-1 at 3.3 GPa. Molecular dynamics simulations suggest that a gradual decrease in viscosity of albite melt at high pressure may be explained by structural changes such as an increase in the coordination number of aluminum in the melt.
Keywords: VISCOSITY; HIGH PRESSURE; MAGMA; SILICATE MELT; MOLECULAR SIMULATION